2012
DOI: 10.2174/1876817201204010011
|View full text |Cite
|
Sign up to set email alerts
|

Seroma Production After Breast Cancer Surgery has a Pro-Inflammatory Component

Abstract: Seroma formation is the most prevalent postoperative sequela after breast cancer surgery. A total of 263 aspirations of seroma fluid in 42 patients were performed after mastectomy; cytokines were measured in 148 cases. The concentration of interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), interleukin-12p70 (IL-12) and tumor necrosis factor (TNF) were measured. The patients underwent 9.0 seroma aspirations on average (range 1-17) during an average of 30.7 days (range 7-72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…In fact, the pathological origin of seromas has not been fully clarified, but has been found to be associated with several factors such as age, BMI, breast size [ 9 ], the type of surgical procedure [ 10 ], and the use of electrocautery [ 14 ]. However, several studies have demonstrated the inflammatory origin of the exudate; it seems likely to be the body's natural response to tissue damage [ 7 , 8 , 9 , 21 , 22 ]. Therefore, our Oncoplastic Breast Surgery Team decided to perform a conservative and delicate surgical technique aimed at reducing tissue trauma in hopes of attenuating the inflammatory response and reduce the variables related to serum production.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pathological origin of seromas has not been fully clarified, but has been found to be associated with several factors such as age, BMI, breast size [ 9 ], the type of surgical procedure [ 10 ], and the use of electrocautery [ 14 ]. However, several studies have demonstrated the inflammatory origin of the exudate; it seems likely to be the body's natural response to tissue damage [ 7 , 8 , 9 , 21 , 22 ]. Therefore, our Oncoplastic Breast Surgery Team decided to perform a conservative and delicate surgical technique aimed at reducing tissue trauma in hopes of attenuating the inflammatory response and reduce the variables related to serum production.…”
Section: Discussionmentioning
confidence: 99%
“…Seroma formation has an acute inflammatory component in response to surgical trauma [3, 4] via the activities of proteinases, proteinase inhibitors, cytokines, and growth factors [5, 6]. In the early postoperative period, seroma fluid slowly becomes exudative with some characteristics similar to those of lymph [7].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, growing evidence has suggested that a seroma is more than the simple accumulation of serous fluid; rather, it is an exudate that forms in response to acute inflammation induced by surgical trauma. This concept is supported by the presence of proteinases, proteinase inhibitors and cytokines in the seroma fluid. Immunomodulatory compounds have been evaluated for the prevention of seroma formation, and have displayed some efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation and proinflammatory cytokines, such as interleukin (IL) 1 and IL‐6, are considered to act as tumour promoters. Interestingly, high levels of the proinflammatory cytokines IL‐6 and IL‐8 have been detected in seroma fluid after breast cancer surgery. Postoperative administration of a steroid may exert an additional beneficial effect if tumour cells remain in the surgical field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation